Kinematic determinants of take-off performance in elite and sub-elite male long jumpers: a competition-based two-dimensional motion analysis - Wei, P.; Yuan, T.; Xie, Z. (Frontiers in Physiology, 2026)
Background: The performance of the long jump depends on the effective conversion of high approach velocity into ballistic flight during brief take-off contact. This process requires rapid force production, efficient stretch-shortening cycle (SSC) function, and precise neuromuscular coordination. The approach speed is widely recognized as key determinant of jump distance. The specific kinematic characteristics which distinguish closely matched high-level athletes under real competition conditions remain unclear. Thus, this study was intended for the identification of key kinematic characteristics associated with take-off performance in elite and sub-elite male long jumpers using competition-based two-dimensional motion analysis.